Approximate expressions for the Green's functions of a semi-infinite, elastic medium - Pliberšek, Tomaž (Acta geotechnica Slovenica, 2010)
On the basis of an exact, discretized presentation of the Green's function components, their closed-form approximations are developed. Their accuracy is considered to be better than the tolerances in the intrusive measurements data for the identification of the mechanical characteristics of soils. The use of these approximate expressions is believed to considerably reduce the computational effort in soil-structure interaction problems and open up new possibilities for the non-intrusive identification of soils
Keywords: aproksimativne rešitve; Greenova funkcija; matematični modeli; mehanika tal